Socially responsible investment strategy of the Norwegian Wealth Fund - Toscano, Diana (2021)
Imagine a student studying in his own country, is awarded a scholarship from a developed foreign country. To continue receiving a scholarship, the student is assessed by the sponsoring country’s education standards and needs to conform. What can we expect to ensue? There is a striking resemblance of this example to this research topic. Sovereign Wealth Funds (SWFs) have been at the center of discussions and controversies due to the capitalistic influence that they exert on portfolio companies and the immense financial space that they operate in. Often termed as activists, capitalists, shareholders, stakeholders, or sponsors, these financial intermediaries, with their heterogeneous motivations, patronize companies in developing countries. Several government-controlled SWFs have acquired stakes worldwide. (Lyons 2008) & (Fry, Mckibbin, and O’Brien 2011). SWFs have also been in the spotlight for the wrong reasons such as lack of accountability or transparency. (Stone and Truman 2016). From initially aiming at profit maximization at inception, SWF’s have evolved to gradually incorporate significant non-financial objectives in their investment strategies. Over the past decade, SWFs are increasingly focusing on socially responsible investing also known as ethical or impact investing. A literature review reveals a limited discussion about SRI implementation by SWFs and even fewer SWFs adopting SRI strategies. The Norwegian SWF hereafter referred to as GPFG, has been regarded as the torchbearer for its highly transparent, viable and successful fund management strategy. With open strategies it has produced results, enhanced market liquidity and acted as a stabilizing influence amongst other SWFs (IMF European Dept Delia Velculescu 2008). Since 2005, the GPFG has voluntarily engaged in socially responsible investing strategies concerning the portfolio companies that they invest in. As a combined effort of its financial and ethical arms, the GPFG evaluates companies according to its ethical guidelines and decides the further course of action of divesting or reinvesting in companies blacklisted by them. Taking into consideration a subset of companies that have been excluded or placed under observation by the GPFG, I aim to investigate the consequences of the GPFG’s strategies. The research involves examining individual company reactions following the GPFG decision. The patterns in the narratives and actions of the company, point towards the actual impact of the GPFG’s decision on the company. Without assuming any theory or phenomenon at the outset, I undertake an interpretative qualitative analysis of GPFG sources, data, along with company annual, sustainability, and governance reports, news articles. Empirical findings lean towards the two main theories – First, institutional decoupling and resource dependence. Besides the theoretical links, an intriguing phenomenon emerges – shareholder primacy prevails.